2016
DOI: 10.1007/s00792-016-0841-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermostable Thermotoga maritima xylanase XYN10B shows high activity at high temperatures in the presence of biomass-dissolving hydrophilic ionic liquids

Abstract: The gene of Thermotoga maritima GH10 xylanase (TmXYN10B) was synthesised to study the extreme limits of this hyperthermostable enzyme at high temperatures in the presence of biomass-dissolving hydrophilic ionic liquids (ILs). TmXYN10B expressed from Pichia pastoris showed maximal activity at 100 °C and retained 92 % of maximal activity at 105 °C in a 30-min assay. Although the temperature optimum of activity was lowered by 1-ethyl-3-methylimidazolium acetate ([EMIM]OAc), TmXYN10B retained partial activity in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
(62 reference statements)
1
24
0
Order By: Relevance
“…However, this enzyme has demonstrated its hydrolytic efficiency in the presence of IL at higher temperatures (80-100 ∘ C). 23 In previous studies and in this study, family GH10 xylanases were generally found to be more IL-tolerant compared with family GH11 enzymes. 35 Earlier findings with [EMIM]AcO suggest that the IL interferes with substrate binding in the active site and this competitive inhibition may be more pronounced with family GH11 xylanases.…”
Section: Screening Of Xylanasessupporting
confidence: 58%
See 3 more Smart Citations
“…However, this enzyme has demonstrated its hydrolytic efficiency in the presence of IL at higher temperatures (80-100 ∘ C). 23 In previous studies and in this study, family GH10 xylanases were generally found to be more IL-tolerant compared with family GH11 enzymes. 35 Earlier findings with [EMIM]AcO suggest that the IL interferes with substrate binding in the active site and this competitive inhibition may be more pronounced with family GH11 xylanases.…”
Section: Screening Of Xylanasessupporting
confidence: 58%
“…Among the studied xylanases TmXYN10B was the most thermostable enzyme, but it was not the most IL‐tolerant one. However, this enzyme has demonstrated its hydrolytic efficiency in the presence of IL at higher temperatures (80–100 °C) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Currie et al., ) are known for decomposing biomass at high temperatures (Bhalla, Bansal, Kumar, Bischoff, & Sani, ). Furthermore, members of the genera Thermotoga (Yu et al., ), Rhodothermus (Keshk, ), Anoxybacillus (Chan et al., ), Rhodothermaceae strain RA (Goh et al., ), and Caldicellulosiruptor (Peng et al., ) were found to produce thermostable enzymes for biomass saccharification.…”
Section: Introductionmentioning
confidence: 99%